4D BIM Simulation Guideline for Construction Visualization and Analysis of Renovation Projects: A Case Study - Alzarrad, M. Ammar; Moynihan, Gary P.; Parajuli, Aakash; Mehra, Mayuri (Frontiers in Built Environment, 2021)
With the BIM applications on fast-track, it is being used for new construction and recently being utilized for renovation, retrofitting, and repairing purposes. Although many studies have been conducted to identify BIM capabilities in renovation projects, the application of 4D BIM for both the demolition and the construction phases of renovation projects is still underdeveloped. This paper presents a guideline to apply 4D BIM for complicated renovation projects that include demolition and construction phases. The paper represents a step-by-step process from the extraction of information from a 2D model and converting it into a 4D model. The proposed guideline will help CAD users to apply 4D BIM for complicated renovation model. A real case application is analyzed to demonstrate the potential of the presented guideline. The research results show that the proposed guideline could assist in construction management by finding out inappropriate sequences in schedule, conducting evaluation of issues related to constructability, and identifying disagreements in time and space. The proposed guideline could help identify errors in construction scheduling, which have the potential to reduce project cost and duration.